Comparison Of Microbiological And Chemical Assay Methods Used In The Quality Assessment Of Ampicillin Suspensions Sold In Zaria-Nigeria - Ejikeme, Udobi Chinweizu; Ademola, Onaolapo, Josiah (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
There appears to be a disagreement between chemists and biologists over which of the methods for the assay of antibiotics is better and more reliable. A total of 27 samples of ampicillin suspension from three different companies comprising nine batches and sold within Zaria-Nigeria were therefore assayed to determine their potency using standard chemical and microbiological methods. Results obtained showed that most of the products were of acceptable quality and also confirmed that each of the two methods compared was as good as the other and can therefore be used for the determination of the quality of ampicillin.